Neonatal mortality rate in Al-ramadi province from Period (2003 to 2013), Retrospective study - Hunnosh, Mohammed M.; ALAkori, Maher M. H.; Al-Ani, Mohamed M. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: neonatal period is the most vulnerable and high risk time in the life because of the highest mortality incidence in human life during this period. Neonatal mortality rate is defined as the number of deaths twenty seven completed days of live per 1000 live births.Objectives: To determine the neonatal mortality rate (NMR) in Al-Ramadi province, the center of Al-Anbar Governorate, Western Iraq, from 2003-2013 with rate comparison of the two different stages of that period.Methods: Data were collected from the births and deaths certificate center in Al- Ramadi province, Western Iraq, included; age, sex, address ,date of birth and cause of death. Data collected in two different periods, the first period from 2003- 2007 and the second period from 2008- 2013. The neonatal mortality rates (NMRs) were analyzed and compared with other studies.Results: The neonatal mortality rate (NMR) of the first period was 34.5/1000 and neonatal mortality rates NMR of the second period was 24.3/1000. During the 11 studied years the higher rate of neonatal mortality was in 2006 (36.8/1000) and lower rate in 2012 (21.3/1000). Approximately two-third of neonatal deaths occurred during the early neonatal period and one third in the late neonatal period. Males had higher neonatal rate (NMR) than females, and rural residence higher than urban.Conclusions: Al-Ramadi province had high neonatal mortality rate comparing with national Iraqi neonatal mortality rate (NMR) ,due to deterioration of socioeconomic and security conditions. There was significant association between NMR and residency and significant association between NMR and gender.